Seeing the whole: configurational cognition and new venture resource mobilization - Calic, Goran; Neville, François; Furnari, Santi; Chan, C.S. Richard; Michael Lee-Chin & Family Institute for Strategic Business Studies (My University, 2023)
Research is scant on how multiple venture attributes combine as “whole packages” of signals (or cognitive configurations) in resource holders’ eyes, shaping a venture’s ability to mobilize resources. Drawing on a Qualitative Comparative Analysis of 1,395 crowdfunding campaigns, we identified different configurations of signals for high and low resource mobilization, theorizing abductively their underlying mechanisms through the analysis of case-level qualitative data. Our results explain some past mixed findings, such as the contradictory effects of social value and entrepreneurial narratives, showing that these narratives can instead be successfully combined in the presence of signals of venture quality and community embeddedness. We show that there is no single best way to impress resource holders, but multiple recipes to holistically communicate a venture’s value. Valuation Insight: Resource mobilization to unlock the value of a planned venture requires persuading investors. Potential investors cognitively combine the multiple observable attributes of the venture to obtain a holistic idea of its underlying value. The promoted attributes of the venture must make sense jointly to attract funding. The analysis uncovers different attribute configurations that may be viewed as entrepreneurial profiles that are equally effective in mobilizing the resources to create the value implicit in the venture plan.
61 p. ; Includes bibliographical references (pp. 40-45)
Keywords: Resource mobilization; Entrepreneurship; Behavioural theory; Fuzzy-set qualitative comparative analysis (fsQCA); Configurational perspective